2018
DOI: 10.1186/s12889-018-6135-9
|View full text |Cite
|
Sign up to set email alerts
|

Pilot field testing of the chronic pain classification for ICD-11: the results of ecological coding

Abstract: BackgroundA task force of the International Association for the Study of Pain (IASP) has developed a classification of chronic pain for the ICD-11 consisting of seven major categories. The objective was to test whether the proposed categories were exhaustive and mutually exclusive. In addition, the perceived utility of the diagnoses and the raters’ subjective diagnostic certainty were to be assessed.MethodsFive independent pain centers in three continents coded 507 consecutive patients. The raters received the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 33 publications
(33 reference statements)
0
36
0
2
Order By: Relevance
“…However, it is important to underline that the applied rating procedure was restricted in that the examiners did not meet the participants and had received no formal training in ICD‐11. Furthermore, the first study on field testing data found a good acceptance of the proposed classification and only few cases with double‐diagnoses (Barke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to underline that the applied rating procedure was restricted in that the examiners did not meet the participants and had received no formal training in ICD‐11. Furthermore, the first study on field testing data found a good acceptance of the proposed classification and only few cases with double‐diagnoses (Barke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations: Despite accessing several years' data from a large pain registry, the number of patients with CRP was relatively small, yet similar to the low rates of referral to pain clinics in other studies. 6 Patients referred to specialist pain clinics may not be generally representative of all patients with CRP. The categorization of patients as having CRP or not was based on their self-report.…”
Section: Discussionmentioning
confidence: 99%
“…The content models were developed by the seven author teams, and were then entered as children of the appropriate parent entities via the WHO proposal platform. Preliminary versions of the classification were 3 The prefinal version was further subjected to the official international field testing of the WHO via the IASP website.…”
Section: Methodsmentioning
confidence: 99%